2016
DOI: 10.1080/23328940.2016.1230171
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia and cardiovascular strain during an extreme heat exposure in young versus older adults

Abstract: We examined whether older individuals experience greater levels of hyperthermia and cardiovascular strain during an extreme heat exposure compared to young adults. During a 3-hour extreme heat exposure (44°C, 30% relative humidity), we compared body heat storage, core temperature (rectal, visceral) and cardiovascular (heart rate, cardiac output, mean arterial pressure, limb blood flow) responses of young adults (n = 30, 19–28 years) against those of older adults (n = 30, 55–73 years). Direct calorimetry measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 41 publications
1
74
1
6
Order By: Relevance
“…As such, we were also able to assess the influence of a passive heat stress on heat loss responses which has been shown to be attenuated in older adults with (Kenny et al. ) and without type 2 diabetes (Kenny et al. ) relative to young adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we were also able to assess the influence of a passive heat stress on heat loss responses which has been shown to be attenuated in older adults with (Kenny et al. ) and without type 2 diabetes (Kenny et al. ) relative to young adults.…”
Section: Methodsmentioning
confidence: 99%
“…; Kenny et al. ). In parallel, although nitric oxide (NO) synthase (NOS) is known to contribute to the regulation of cutaneous vasodilation (Kellogg et al.…”
Section: Introductionmentioning
confidence: 97%
“…Studies employing whole‐body direct calorimetry have demonstrated that older adults store more heat during simulated heat wave conditions relative to young adults (Kenny et al., ; Stapleton et al., ). Interestingly, greater heat storage in older adults was mediated solely through greater dry heat gain in these studies as sweat evaporation was similar to young adults.…”
Section: Introductionmentioning
confidence: 99%
“…The ventilatory and heart rate responses to hypoxia and hypercapnia diminish in old age, with a reduction in adrenergic responses (Kenny et al . ). The age‐dependent reduction in breathing capacity is evident, causing tissue hypoxia.…”
mentioning
confidence: 97%